Increase of dynamic stability of a basis at operation of the compressor equipment of the Abazіvka unit of complex gas preparation - Mykhailovska, Olena; Zotsenko, Mykola (Technology audit and production reserves, 2021)
The object of research is the basis of the compressor equipment of the complex gas treatment plant at the Abazivka field and the strengthening of the base soils with soil-cement elements, which are proposed to be arranged with the use of drilling technology. The research area is located on the territory of the current Abazivka Integrated Gas Preparation, near the village of Bugaivka, Poltava region, Ukraine. Abazivka Integrated Gas Preparation receives products from wells in Abazivka and Sementsivske deposits. It is proposed to carry out the reconstruction of Integrated Gas Preparation, which includes strengthening the foundation of the compressor model C1004-JGT/2-1 manufactured by «Propak» (Alberta, Canada). The amplitudes of oscillations of the compressor foundation were determined at a speed of 1400 rpm at the appropriate site with geological conditions. The magnitudes of oscillations and subsidence of the compressor foundation of the Abazivka complex of complex gas treatment were investigated experimentally. When determining the amplitudes of oscillations of the compressor foundations, only the amplitudes of oscillations in the direction parallel to the sliding of the pistons were calculated, and the influence of the vertical component of the perturbing forces was not taken into account. It is established that the amplitude of horizontal-rotational oscillations of the upper face of the compressor foundation relative to the horizontal axis exceeds the maximum allowable. It is substantiated that soil cement is a sufficiently strong and waterproof material that can be used to strengthen the base during the construction of equipment foundations. The possibility of application of the technology of application of soil-cement piles, made by brown-mixing technology for strengthening the base under the foundation of the compressor, is described and investigated. It is proposed to reinforce the base with rows of soil-cement elements, which will increase the modulus of deformation of the base, which is represented by loam, light to 14.3 MPa. In the case of strengthening the base, the amplitude of horizontal-rotational oscillations of the upper face of the compressor foundation is much less than the maximum allowable 0.1 mm. The subsidence of the foundation at reinforcement of the base, which does not exceed the maximum allowable value, is determined. Soil-cement elements are proposed to be arranged according to the drilling technology.